Peran Peradilan Agama Sebagai Penegak Hukum Islam Di Indonesia - Hoerurojikin, Mohamad (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
The existence of Religious Courts as Islamic judicial institutions has an influence on the Islamic community in obtaining justice. Therefore, Law No. 50 of 2009, which is the second amendment to Law No. 7 of 1989 on Religious Courts, has become an important milestone for the supremacy of Religious Courts law in Indonesia. Generally, the sources of law in Religious Courts consist of material sources derived from Islamic law and material sources bound by Law No. 50 of 2009. Formal legal sources include statutory law, custom law, jurisprudence law, religious law, and customary law recognized as positive law. The authority to examine, decide, and settle cases at the first level for individuals who are Muslims is the responsibility of Religious Courts, based on relative authority and absolute authority.